Estudo da ruptura dielétrica durante a anodização de zircônio e o seu efeito sobre o processo de dopagem anódica de ZrO2 - Santos, Janaina Soares (2012)
In this work the fundamental aspects of electrolytic breakdown in ZrO2 films were investigated. The electrolytic breakdown is a type of dielectric breakdown that occurs during galvanostatic growth of anodic oxides. To perform this investigation, the study was divided in two parts: (i) the modification of ZrO2 films by anodic doping and (ii) characterization of the electrical discharges (sparks) that appears on the electrode surface during zirconium anodization. The anodic doping study aimed to monitor the system and analyze the influence of current density, temperature and dopant concentration on the electrochemical, morphological and microstructural properties of ZrO2 films doped with calcium and niobium ions. The factorial design technique was used to optimize the number of experiments and quantify the effects of experimental variables on the responses. The results showed that all variables influenced the electrochemical response, leading to changes in morphology and microstructural properties of the ZrO2 doped films. This result was observed because these variables can affect the mobility of ionic species, ionic transport inside the oxide, the electrolyte resistivity and the dissolution process of the oxide. The spark characterization study aimed to investigate the evolution of electrical discharges during the experiment and correlate them with the processes observed in the anodization curve of zirconium. Hence, the electrode surface was recorded during the experiments using a high definition and high speed video camera. The image analysis allowed the calculation of the size, quantity and lifetime of the sparks discharges. Due to the enormous amount of data, it was necessary to develop a new methodology to analyzing the results. The methods used were based on techniques of imaging processing and multivariate data analysis. The use of these techniques coupled to electrochemical ones provided new insights that elucidated some aspects of the breakdown phenomenon. Furthermore, it provided guidelines for the implementation of future work.